Faktor Penentu Keberhasilan Proyek KPBU Penerangan Jalan Umum: Studi Komparatif antara Kabupaten Dharmasraya dan Kabupaten Sijunjung - Kurniawan, Deny; Tan, Firwan; N, Zulkifli (SAFE-Network, 2025)
This study aims to analyze the critical success factors of Public-Private Partnership projects in the provision of Public Street Lighting infrastructure through a comparative case study in Dharmasraya and Sijunjung Regencies, West Sumatra Province. The research method employed is causal-comparative with a quantitative approach, utilizing questionnaires, interviews, and documentation involving stakeholders in the PPP projects. Data analysis was conducted using a paired t-test to examine differences in perceptions between the two regencies across 18 success factor variables. The results show that Dharmasraya Regency demonstrated a higher level of success in implementing the PPP PJU project compared to Sijunjung, particularly in aspects such as government commitment, political support, accountability, delegation of authority, and public support. Meanwhile, several factors such as lighting efficiency, clarity of cooperation agreements, and project feasibility did not show significant differences between the regions. These findings highlight the importance of institutional, social, and political support in ensuring the success of PPP projects at the local level. The study recommends enhancing the capacity of PPP project teams and strengthening budgetary commitments in each region as strategic steps to improve the effectiveness of similar future projects.